Daring to Compete - Foreman, Diane; Pearce, Bryan; Godding, Geoffrey (Ascent Audio, 2019)
The successful entrepreneur's guide to accelerating growth Daring to Compete offers real-world strategies to accelerate the growth of your business and secure your place as a market leader. This expert guide is the result of years of comprehensive research and experience from global professional services organization EY, originator of the celebrated "Entrepreneur Of The Year" program. Employing its worldwide reach and extensive network of successful entrepreneurs, EY has developed a model of sustainable business development-"The 7 Drivers of Growth." This innovative and highly effective approach to strategic growth is an invaluable resource for high-growth businesses, entrepreneurs, and start-ups. Favoring practical strategies over abstract theories, this book provides clear guidance on the Customer; Funding and Finance; Transactions and Alliances; Risk; People, Behaviors, and Culture; Digital Technology and Analytics; and Operations. This book brings the application of these drivers to life by featuring insights from Entrepreneur Of The Year award-winning entrepreneurs from a wide range of industries and geographic locations. These entrepreneurs share how each driver functions in actual business situations and present first-hand advice on their application and implementation.